Investigation of (100) In₄Se₃ crystal surface nanorelief - Galiy, P.V.; Ciszewski, A.; Dveriy, O.R.; Losovyj, Ya.B.; Mazur, P.; Nenchuk, T.M.; Zuber, S.; Fiyala, Ya.M. (Functional Materials, 2009)
The crystallography and topography of the (100) cleavage surfaces of layered semiconductor In₄Se₃ crystal have been studied by low energy electron diffraction (LEED), scanning tunnelling and atomic-force microscopy (STM, AFM) in ultrahigh vacuum (UHV). The structure of surface LEED patterns, shape and dimensions of subsequent STM- and AFMprofiles agree well with the lattice parameters derived from the bulk crystal structure obtained by X-ray diffraction. The local density of states and band gap for (100) In₄Se₃ have been obtained by scanning tunnelling spectroscopy and point to the same integral gap value as for bulk crystal. The STM/STS results evidence the stability of interlayer cleavage surface and confirm that anisotropic striated low conductive cleavage surfaces might be suitable as matrices/templates in formation of surface nanowires or nanostructures.